Caffeic Acid Phenethyl Ester Loaded PLGA Nanoparticles: Effect of Various Process Parameters on Reaction Yield, Encapsulation Efficiency, and Particle Size - Derman, Serap (HINDAWI LTD, 2015)
CAPE loaded PLGA nanoparticles were prepared using the oil in water (o/w) single emulsion solvent evaporation methods. Five different processing parameters including initial CAPE amount, initial PLGA amount, PVA concentration in aqueous phase, PVA volume, and solvent type were screened systematically to improve encapsulation of hydrophobic CAPE molecule, simultaneously minimize particle size, and raise the reaction yield. Obtained results showed that the encapsulation efficiency of the nanoparticles significantly increased with the increase of the initial CAPE amount (p < 0.05) and particle size (p < 0.05). Furthermore, the particle size is significantly influenced by initial polymer amount (p < 0.05) and surfactant concentration (p < 0.05). By the optimization of process parameters, the nanoparticles produced 70 +/- 6% reaction yield, 89 +/- 3% encapsulation efficiency, -34.4 +/- 2.5 mV zeta potential, and 163 +/- 2 nm particle size with low polydispersity index 0.119 +/- 0.002. The particle size and surface morphology of optimized nanoparticles were studied and analyses showed that the nanoparticles have uniform size distribution, smooth surface, and spherical shape. Lyophilized nanoparticles with different CAPE and PLGA concentration in formulation were examined for in vitro release at physiological pH. Interestingly, the optimized nanoparticles showed a high (83.08%) and sustained CAPE release (lasting for 16 days) compared to nonoptimized nanoparticle.
Keywords: NF-KAPPA-B; EMULSIFICATION-DIFFUSION; FORMULATION VARIABLES; HYDROPHOBIC DRUGS; RELEASE BEHAVIOR; IN-VITRO; SOLVENT; MICROSPHERES; APOPTOSIS; INHIBITORS; Science & Technology - Other Topics; Materials Science